Recent advances in drug delivery systems based on polypeptides prepared from N‐carboxyanhydrides. Issue 6 (3rd March 2014) - Hehir, Sarah; Cameron, Neil R
<x xml:space="preserve">Abstract</x> Multifunctional polypeptide‐based drug delivery systems prepared from ring‐opening polymerization of N‐carboxyanhydrides demonstrate enormous potential in the drug delivery field, incorporating increased biostability along with stimuli‐responsive and active targeting functions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>